The impact of payment methods and payment-related marketing communications on e-commerce retailer trust - an empirical consumer analysis of Indonesian e-commerce start-ups. (15th September 2021) - Lakeman, Farrah Almira; Walter, Nadine; Cleff, Thomas
The purpose of this paper is to investigate preferences of online payment methods of consumers using e-commerce websites of start-up companies in Indonesia. A quantitative online survey was used and 215 valid responses from e-commerce consumers in Indonesia were generated. The study confirms the positive impact of trust on the online purchase decision. It also reveals that convenience of online payment methods positively influences the level of trust in e-commerce start-ups. This was confirmed for access and transaction convenience. Payment-related marketing communication also proves to generate trust - information dissemination about payment methods throughout the customer journey (before the check-out) and the usage of assurance seals are particularly important.